2016
DOI: 10.1016/j.eats.2015.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Osgood-Schlatter Disease

Abstract: Osgood-Schlatter disease is a common cause of anterior knee pain in sports-practicing adolescents. The long-term outcomes have not always been favorable, and some adolescents have persisting knee pain into adulthood. Excision of the ossicle together with debridement of the tibial tuberosity is indicated if the pain is not relieved with conservative measures. An endoscopic technique for excision of the ossicle associated with Osgood-Schlatter disease is reported. It has the advantages of avoidance of painful su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
8
2
Order By: Relevance
“…Based on their research, Ogden et al [ 3 ] and Lui et al [ 26 ] found that OSD usually manifests itself in adolescence and is characterized by multifactorial genesis, irregular course, and long duration of the disease, even up to several years, which was not confirmed in the present case. Circi et al [ 12 ] indicated that OSD resolved spontaneously after the closure of the tibial growth plate, which is not consistent with our results because OSD did not manifest itself until after the second growth spurt, and the 20-month therapeutic and preventive intervention allowed for recovery.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Based on their research, Ogden et al [ 3 ] and Lui et al [ 26 ] found that OSD usually manifests itself in adolescence and is characterized by multifactorial genesis, irregular course, and long duration of the disease, even up to several years, which was not confirmed in the present case. Circi et al [ 12 ] indicated that OSD resolved spontaneously after the closure of the tibial growth plate, which is not consistent with our results because OSD did not manifest itself until after the second growth spurt, and the 20-month therapeutic and preventive intervention allowed for recovery.…”
Section: Discussioncontrasting
confidence: 67%
“…Circi et al [ 12 ] indicated that OSD resolved spontaneously after the closure of the tibial growth plate, which is not consistent with our results because OSD did not manifest itself until after the second growth spurt, and the 20-month therapeutic and preventive intervention allowed for recovery. Furthermore, Lui et al [ 26 ] found persistent OSD symptoms in adulthood, which is also not the case in the present study, and the athlete continues to practice the sport and be successful at an elite level.…”
Section: Discussioncontrasting
confidence: 52%
“…Meanwhile, arthroscopic surgery has been associated with several advantages, including small incisions, minimal wound pain and scarring, and accelerated functional recovery. 7 However, its disadvantages include possible damage to the infrapatellar fat pad, anterior horn of the meniscus, and intermeniscal ligament. 8 In addition to open and arthroscopic surgery, bursoscopic surgery also has become available.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention in this group could induce unnaturally early fusion of the tibial tubercle 28. However, when symptoms persist after physeal closure, or remain unresolved or disabling after adequate conservative therapy, surgical treatment can be considered 44,47,48. Surgery must be avoided in patients with diffused anterior knee pain because the condition may be caused by other pathologies, such as chondromalacia patellae 44,49…”
Section: Treatmentmentioning
confidence: 99%
“…Conservative treatment of OSD should focus on reducing stress on the tibial tubercle and tension in the quadriceps muscle. 28,44 This treatment includes icing, activity modification, oral or local nonsteroidal antiinflammatory drugs, and physical therapy. 25,31 Rest or immobilization is not proven to speed up the recovery, but activity restriction appears effective in reducing pain.…”
Section: Conservative Treatmentmentioning
confidence: 99%